A blockchain-based deep learning-empowered optimal auction platform - Li, Zhaonian (Nanyang Technological University, 2022)
This project focuses on the optimisation of sealed-bid second price auction. Not only does the goodness of second price auction be retained, but the application will also utilise blockchain and a decentralised application to provide a fair and transparent data storing environment. Moreover, the winner of the auction and the payment price is determined by a deep learning model which maximises the seller’s revenue in a forward auction and minimises the buyer’s cost in a reverse auction.